Comparison of Sphincter Saving Resection (SSR) & Sphincter Losing Abdominoperineal Resection (APR) in Very Low Rectal Cancer (Journal of Shaheed Suhrawardy Medical College, 2019)
Oncological outcomes of sphincter-saving resection (SSR) and sphincter losing abdominoperineal resection (APR) in 210 consecutive patients with very low-lying rectal cancer (i.e. lower margin of tumor is within 3.5 cm from the anal verge) were studied and compared. 54 (25.71%) patients underwent SSR and 156 (74.28%) patients underwent SLR-APR. The APR group comprised higher proportions of men (61.53% vs 55.5%, P =.049) and advanced-stage disease (P